2023
DOI: 10.3390/ijms24065623
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Diffuse Large B-Cell Lymphoma Cells Inducibly Expressing MyD88 L265P Mutation Identifies Upregulated CD44, LGALS3, NFKBIZ, and BATF as Downstream Targets of Oncogenic NF-κB Signaling

Abstract: During innate immune responses, myeloid differentiation primary response 88 (MyD88) functions as a critical signaling adaptor protein integrating stimuli from toll-like receptors (TLR) and the interleukin-1 receptor (IL-1R) family and translates them into specific cellular outcomes. In B cells, somatic mutations in MyD88 trigger oncogenic NF-κB signaling independent of receptor stimulation, which leads to the development of B-cell malignancies. However, the exact molecular mechanisms and downstream signaling t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 201 publications
0
7
0
Order By: Relevance
“…IFNAR signals, however, may only contribute to Batf expression in pDCs in the presence of a second signal induced by TLR9 activation in pDCs. Previous studies have demonstrated the requirement of the TLR4/MyD88-NFκB axis for induction of BATF expression in a B cell line 35, 36, 37 . In addition, also cytokines such as IL-10, LIF, IL-6, IL-7, and IL-21, which signal through Jak/Stat signaling pathways, have been shown to induce BATF in various cell types 38, 39, 40 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…IFNAR signals, however, may only contribute to Batf expression in pDCs in the presence of a second signal induced by TLR9 activation in pDCs. Previous studies have demonstrated the requirement of the TLR4/MyD88-NFκB axis for induction of BATF expression in a B cell line 35, 36, 37 . In addition, also cytokines such as IL-10, LIF, IL-6, IL-7, and IL-21, which signal through Jak/Stat signaling pathways, have been shown to induce BATF in various cell types 38, 39, 40 .…”
Section: Discussionmentioning
confidence: 96%
“…In addition, also cytokines such as IL-10, LIF, IL-6, IL-7, and IL-21, which signal through Jak/Stat signaling pathways, have been shown to induce BATF in various cell types 38, 39, 40 . Strikingly, blocking the NFκB activity by specifically inhibiting TAK1 or Stat3 and Stat6 functions abrogated Myd88 mediated BATF expression in Large B-cell Lymphoma cells 37 or IL-7-induced BATF expression in innate lymphoid cell (ILC) progenitors 16 , respectively. In addition, Notch signaling has also been associated with BATF expression in B cells 41 .…”
Section: Discussionmentioning
confidence: 99%
“…The GEO database and TCGA database are popular and widely used biomedical information repositories, covering nearly all genomics, transcriptomics, proteomics, epigenetics, and other omics data related to organs, tissues, and cells. They are the largest and most comprehensive tumor gene information databases globally ( 28 , 29 ) and thus have greatly improved the early diagnosis and prevention of cancer by providing support for the in-depth understanding of cancer’s pathogenic factors and mechanisms from molecular and genetic perspectives ( 30 , 31 ). In recent years, researchers have integrated and analyzed data to uncover the pathogenic mechanisms of related tumors.…”
Section: Discussionmentioning
confidence: 99%
“…NFKBIZ played a bidirectional role in the progression of divergent tumors. Research on diffuse large B-cell lymphoblastoma (DLBCL) proposed that approximately 40% of primary testicular DLBCL (PT-DLBCL) patients were accompanied by NFKBIZ somatic cell mutations, and the abnormal expression of NFKBIZ promoted PT-DLBCL advancement [ 7 , 8 ]. Notably, the mutation rate of NFKBIZ was higher in intestinal epithelial cells in the context of ulcerative colitis, but lower in colitis-led tumor cells, suggesting that intestinal epithelial cells may resist tumor transformation through selective NFKBIZ mutation [ 9 ].…”
Section: Introductionmentioning
confidence: 99%